Respuesta :

elit4

-----------------------------------------------------------------------------------------------------------------

Answer: n = -1

-----------------------------------------------------------------------------------------------------------------

add 6 to both sides of the equation.

4n − 6 = 10n

4n − 6 + 6 = 10n + 6

-----------------------------------------------------------------------------------------------------------------

simplify.

(add the numbers)

4n − 6 + 6 = 10n + 6

4n = 10n + 6

4n = 10n + 6

-----------------------------------------------------------------------------------------------------------------

subtract 10n from both sides.

4n − 10n = 10n + 6 − 10n

-----------------------------------------------------------------------------------------------------------------

simplify. (again)

(combine like terms)                                          (combine like terms)

4n − 10n = 10n + 6 − 10n                                   −6n = 10n + 6 − 10n

−6n = 6

-----------------------------------------------------------------------------------------------------------------

divide both sides by the same term.

−6n/−6 = 6/-6

n = 6/−6n = 6/−6

-----------------------------------------------------------------------------------------------------------------

simplify. (again)

(cancel terms that are in both the numerator and denominator)

n = 6/−6

(divide the numbers)

n = 6/−6

n = 1

-----------------------------------------------------------------------------------------------------------------

Answer:

n= -1

Step-by-step explanation: